Hydraulic fracturing explained : evaluation, implementation, and challenges - Donaldson, Erle C. (Gulf Publishing Company, 2013)
Rocks mechanics legend Erle Donaldson, along with colleagues Waqi Alam and NasrinBegum from the oil and gas consultant company Tetrahedron, have authored this handbookon updated fundamentals and more recent technology used during a common hydraulicfracturing procedure. Meant for technical and non-technical professionals interested in thesubject of hydraulic fracturing, the book provides a clear and simple explanation of thetechnology and related issues to promote the safe development of petroleum reservesleading to energy independence throughout the world.
Keywords: Oil wells -- Hydraulic fracturing.; elektronické knihy; electronic books